Why should gender-sensitive health reports be intersectional?. (30th September 2020) - Merz, S; Jaehn, P; Mena, E; Pöge, K; Strasser, S; Saß, A C; Rommel, A; Bolte, G; Holmberg, C
Abstract: Background: A key focus of both epidemiology and PHMR is the identification of health inequity between population groups and its determinants. However, scholars in the social sciences have criticised prevalent approaches of describing health differences according to single social categories like sex/gender or race/ethnicity, glossing over significant heterogeneity within and relations between presumed population groups. Applying these critiques to the field of PHMR, we would argue that intersectionality scholarship offers vital impulses for the study of health inequity by focusing on several, interrelated social categories and emphasising the structural determinants affecting unique population subgroups differently. Methods: We mapped existing approaches to describing population differences in health. We also conducted a literature review on intersectionality scholarship in public health and then synthesised results to develop a conceptual framework for deploying intersectionality to epidemiology and PHMR. Findings: We identified four key principles through which the reporting on subgroup differences could be strengthened: addressing the internal heterogeneity of population groups; contextualising inequities and focusing on societal power relations rather than individual characteristics; deploying novel multivariable modelling approaches in data analysis; and aiming towards the empowerment of population groups rather than deploying deficit-oriented and paternalistic models. Discussion: To be discussed are the unique contributions of intersectionality to PHMR compared to other approaches, for example from social epidemiology or medical anthropology.